Schiff base substituted non-peripheral symmetrical cupper, cobalt, and manganese phthalocyanines: Synthesis, design, electrochemistry, and spectroelectrochemistry - KURTULUŞ, ZEHRA; KOCA, ATIF (My University, 2025)
Novel CoII (nANTH[sbnd]CoPc), CuII (nANTH[sbnd]CuPc), and MnIIICl (nANTH-MnClPc) phthalocyanines were obtained by substituting the 3-(4-((1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-ylimino)methyl)phenoxy) Schiff base compound (nANTH[sbnd]OH) obtained by the acid-catalyzed condensation reaction of 4-aminoantipyrine and 4-hydroxybenzaldehyde at non-peripheral positions. By using various spectroscopic techniques, (NMR, MALDI-TOF, FT-IR, and UV–Vis), the structures of green-colored phthalocyanine compounds and precursor phthalonitrile compounds were identified. The electrochemical responses of cobalt (II) (nANTH[sbnd]CoPc), cupper (II) (nANTH[sbnd]CuPc), and manganese (III) (nANTH-MnClPc) phthalocyanines were determined, and their redox responses were analyzed based on the different metal centers. The results indicated that using redox-active Co2+ and Mn3+ cations instead of Cu2+enhanced the redox richness of the complexes due to the observation of extra metal-based electron transfer reactions in addition to the Pc-based ones. In-situ spectroelectrochemical analyses of the complexes were used to support the peak assignments of the redox processes and the spectrum and color of the electrogenerated species during the redox reactions. Supported these redox mechanisms. Multi-electron transfer processes and distinct color changes during these processes indicate the possible usage of these complexes in various electrochemical and opto-electrochemical processes. Metal-based electron transfer reactions illustrated different spectral changes than those of the Pc-based ones, and these spectral changes significantly differed the color of the anionic and cationic species.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (Sci); Kimya İnorganik Ve Nükleer; Kimya Analitik; Kimya Organik; Natural Sciences (Sci); Chemistry Inorganic & Nuclear; Chemistry Analytical; Chemistry Organic; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Electrochemistry; Phthalocyanines; Schiff bases; Spectroelectrochemistry